TURNING EXPOSURE INTO STREAMS: THE ROLE OF COLDPLAY’S BRAND AWARENESS MEDIATING THE IMPACT OF SOCIAL MEDIA ON LISTENING INTENTIONS - Alan Iksan Ilyasa; Muhammad Fajar Wahyudi Rahman (Journal Informatic, Education and Management (JIEM), 2026)
This study examines the role of brand awareness in mediating the effect of social media music exposure on listening intention by positioning the band Coldplay as a human brand based on the Stimulus-Organism-Response (SOR) model. Employing a quantitative approach, data from 215 active social media users who are university students in Surabaya were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research results confirmed all hypotheses: (1) social media music exposure has a positive and significant effect on listening intention; (2) social media music exposure has a positive and significant effect on brand awareness; (3) brand awareness has a positive and significant effect on listening intention; and (4) brand awareness successfully mediates the effect of social media music exposure on listening intention. These findings assert that background audio exposure in social media content serves as a crucial cognitive bridge, indicating that music marketing strategies need to optimize these platforms to transform passive users into active listeners.